Solid state photochromism of spiropyrans - B. S. Lukyanov; A. V. Metelitsa; N. A. Voloshin; Yu. S. Alexeenko; M. B. Lukyanova; G. T. Vasilyuk; S. A. Maskevich; E. L. Mukhanov (International Journal of Photoenergy)
A series of spiropyrans possessing photochromic properties in solid state were investigated. UV irradiation (λmax=365 nm) of the thin vacuum deposited spiropyran films results in conversion of the colorless form to the photocolored one. The reaction is photochemically and thermally reversible. The photochromic activity of the solid material and polystyrene matrix has been compared. Raman spectroscopy has been used for studying the influence of metallic surface on the adsorbed spiropyran layers.